Does Insider Trading Raise Market Volatility? - Wei, Shang-Jin (IMF Working Papers; Working Paper ;, 2003)
This paper studies the role of insider trading in explaining cross-country differences in stock market volatility. The central finding is that countries with more prevalent insider trading have more volatile stock markets, even after one controls for liquidity/maturity of the market and the volatility of the underlying fundamentals (volatility of real output and of monetary and fiscal policies). Moreover, the effect of insider trading is quantitively significant when compared with the effect of economic fundamentals.